Вы находитесь на странице: 1из 3

Mathematical induction

The basic idea of mathematical induction is this: Suppose you wish to prove that a statement is true of all positive integers. You can easily prove that it is true for the integer k=1. You can also prove that in general, if it is true of the integer k, then it is also true of the integer (k+1). This means that you have proven that if it is true for the integer k=1, then it is also true of the integer k=2. Since you have proven the general step, if it is true of integer k, it is true of the integer (k+1), you have also proven, If it is true of the integer 2, then it is true of the integer 3. If it is true of the integer 3, then it is true of the integer 4. If it is true of the integer 4, then it is true of the integer 5. If it is true of the integer 5, then it is true of the integer 6. etc. In this way you automatically ascend to every finite positive integer. That is you have proven that the statement is true for all positive integers. This is why mathematical induction works. If you prove the statement is true of the integer 1, and you also prove, in general, that whenever the statement is true of the integer k, it is also true of the integer (k+1), then you have therefore proven that it is true of all positive integers. One example frequently given is to prove that for all positive integers n, that 1 + 2 + 3 + 4 + .... + n = n*(n+1)/2 It's easy to prove this formula for the integer k = 1. 1 = 1 *2/2 Now suppose that in general we know that it is true for an integer k.

That is, we know that 1 + 2 + 3 + .... + k = k * (k+1)/2 This is different than what we were asked to prove. We were asked to prove that the formula is true for all positive integers. We presume that it is true for some one unspecified integer k. In fact we know it is true for one specified integer, namely the integer 1. Then we are to use that presumption that it is true for some unspecified integer k, to prove that it is also true for the integer (k+1). In this example, we proceed as follows. We are to prove that 1 + 2 + 3 + .... + k + (k+1) = (k+1)*(k+2)/2 1 + 2 + 3 + ..... + k = k * (k+1)/2 We replace the 1 + 2 + 3 + ..... + k in 1 + 2 + 3 + .... + k + (k+1 k * (k+1)/2 which gives us the equation 1 + 2 + 3 + .... + k + (k+1) = k * (k+1)/2 + (k+1) By factoring out the (k+1) we get 1 + 2 + 3 + .... + k + (k+1) = k * (k+1)/2 + (k+1) = ( k * 1/2 + 1) * (k+1) Note that we can simplify ( k * 1/2 + 1) to (k/2 + 1) = (k+2)/2 That is, we now have 1 + 2 + 3 + .... + k + (k+1) = k * (k+1)/2 + (k+1) = ( k * 1/2 + 1) * (k+1) = ( (k+2)/2) * (k+1) which is also, by changing the order of multiplication, (k+1)*(k+2)/2 equal to given that

by

Thus , we have proven that 1 + 2 + 3 + .... + k + (k+1) = k * (k+1)/2 + (k+1) = ( k * 1/2 + 1) * (k+1) = ( (k+2)/2) * (k+1) = (k+1)*(k+2)/2 which proves that the formula is valid for (k+1). That is, we have proven that if the formula is valid for an unspecified integer k, then it is also true of (k+1). This completes the mathematical induction because we can follow the chain true of 1 ==> true of 2 ==> true of 3 ==> true of 4 ==> .....

Вам также может понравиться